Ag-Based Synergistic Antimicrobial Composites. A Critical Review - Kukushkina, Ekaterina A. (Nanomaterials (Basel), 2021)
The emerging problem of the antibiotic resistance development and the consequences that the health, food and other sectors face stimulate researchers to find safe and effective alternative methods to fight antimicrobial resistance (AMR) and biofilm formation. One of the most promising and efficient groups of materials known for robust antimicrobial performance is noble metal nanoparticles. Notably, silver nanoparticles (AgNPs) have been already widely investigated and applied as antimicrobial agents. However, it has been proposed to create synergistic composites, because pathogens can find their way to develop resistance against metal nanophases; therefore, it could be important to strengthen and secure their antipathogen potency. These complex materials are comprised of individual components with intrinsic antimicrobial action against a wide range of pathogens. One part consists of inorganic AgNPs, and the other, of active organic molecules with pronounced germicidal effects: both phases complement each other, and the effect might just be the sum of the individual effects, or it can be reinforced by the simultaneous application. Many organic molecules have been proposed as potential candidates and successfully united with inorganic counterparts: polysaccharides, with chitosan being the most used component; phenols and organic acids; and peptides and other agents of animal and synthetic origin. In this review, we overview the available literature and critically discuss the findings, including the mechanisms of action, efficacy and application of the silver-based synergistic antimicrobial composites. Hence, we provide a structured summary of the current state of the research direction and give an opinion on perspectives on the development of hybrid Ag-based nanoantimicrobials (NAMs).